2014
DOI: 10.1371/journal.pone.0093797
|View full text |Cite
|
Sign up to set email alerts
|

ASIC2 Subunits Facilitate Expression at the Cell Surface and Confer Regulation by PSD-95

Abstract: Acid-sensing ion channels (ASICs) are Na+ channels activated by changes in pH within the peripheral and central nervous systems. Several different isoforms of ASICs combine to form trimeric channels, and their properties are determined by their subunit composition. ASIC2 subunits are widely expressed throughout the brain, where they heteromultimerize with their partnering subunit, ASIC1a. However, ASIC2 contributes little to the pH sensitivity of the channels, and so its function is not well understood. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 63 publications
6
16
0
Order By: Relevance
“…ASIC2a generated distinct currents in response to an extracellular pH drop to 5.0 or more acidic pH, while ASIC3 displayed higher sensitivity to protons; the half-maximal pH value (pH 50 ) of the ASIC3 transient currents was 6.1 ± 0.2 (n=5), while the pH-dependency curve of ASIC2a did not reach a plateau even at pH 4.0, as previously reported (Fig. 3B) (22). The sustained currents of ASIC3 were steadily increased by a decreasing extracellular pH value, and it was significantly increased when a pH pulse of 4.0 was applied (Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…ASIC2a generated distinct currents in response to an extracellular pH drop to 5.0 or more acidic pH, while ASIC3 displayed higher sensitivity to protons; the half-maximal pH value (pH 50 ) of the ASIC3 transient currents was 6.1 ± 0.2 (n=5), while the pH-dependency curve of ASIC2a did not reach a plateau even at pH 4.0, as previously reported (Fig. 3B) (22). The sustained currents of ASIC3 were steadily increased by a decreasing extracellular pH value, and it was significantly increased when a pH pulse of 4.0 was applied (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Recently, it has been reported that ASIC2a enhances the surface expression of ASIC1a (22, 23). To test whether ASIC2a can also deliver ASIC3 to the cell surface, we co-expressed ASIC2a and ASIC3 in HEK293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, ASIC1a and ASIC3 are the most sensitive to H + channel proteins of these subunits than other ASIC members, which are activated by pH levels below 7.0 [33]. In contrast to ASIC1a homomers, ASIC2a shows low sensitivity to reduced extracellular pH (pH50=4.35) and slow channel inactivation [34,35]. Moreover, homomeric ASIC2a displays slower kinetics of desensitization than ASIC1a homomers [36,37].…”
Section: Structure and Characteristics Of Asicsmentioning
confidence: 99%
“…ASIC2b does not form functional ion channels by itself, distinct from homomeric ASIC2a subunits [19]. On the other hand, ASIC2b associates with other ASIC subunits to form heteromultimeric channels with unique functional properties [19,35]. ASIC3 is primarily expressed in peripheral sensory neurons and plays an important role in pain perception, particularly high-intensity pain stimulation and acid-induced hyperalgesia [38].…”
Section: Structure and Characteristics Of Asicsmentioning
confidence: 99%
“…When ASIC2a heteromultimerizes with other subunits, it reduces pH sensitivity. Furthermore, ASIC2 subunits facilitate subcellular localization of ASIC channels (Harding, Kusama, Hattori, Gautam, & Benson, 2014) through the interaction between ASIC2 and the neuronal scaffolding protein PSD-95, thus increasing ASIC1a localization in dendritic spines (Zha et al, 2009).…”
Section: Discussionmentioning
confidence: 99%